The Arab Spring: Membaca Kronologi dan Faktor Penyebabnya - Sahide, Ahmad; Hadi, Syamsul; Setiawati, Siti Mutiâ€™ah; Cipto, Bambang (Jurnal Hubungan Internasional, 2015)
The Arab States has faced political turbulence since January 0f 2011. This political event began by suicide action from a youth named Mohammed Bouazizi (Tunisia)until it spread to the other states such as Egypt, Syria, and the like. The political event became the beginning of the people power to fight against dictator regime in most of the Arab States. The rise of the people power succeeded to end the power of some tyrannical regimes, beginning from Tunisia, Zein Al-Abidin Ben Ali, followed by the end of Mubarakâ€™s regime in Egypt, Syria still having political turbulence until now in order to overthrow Bashar al-Assadâ€™s regime, and some other Arab States which canâ€™t be irrespective from the political turbulence. This political event is called â€œThe Arab Springâ€, that is the coming of the hope for the better life with a democratic system. This writing tries to discuss chronology of that event and also tries to find out factors becoming cause of the political turbulence.